2019
DOI: 10.1016/j.heliyon.2019.e01730
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of submerged fermentation process for improved production of β-carotene by Exiguobacterium acetylicum S01

Abstract: Carotenoids are natural pigments with substantial applications in nutraceutical, pharmaceutical, and food industries. In this study, optimization of the fermentation process for enhancement of β-carotene and biomass production by Exiguobacterium acetylicum S01 was achieved by employing statistical designs including the Placket-Burman design (PBD) and response surface methodology (RSM). Among the seven variables investigated by two levels in PBD, glucose, peptone, pH and temperature were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Scale-up production of bacterial ALP. Bioreactors, often regarded as the heart of the fermentation process, have helped researchers overcome issues facilitating the scale-up of submerged fermentation from a shake flask to production scale 39 . As this work aims to establish a large-scale fermentation system to evaluate the kinetics of microbial growth in a submerged cultivation system, both shake-flask and stirred-bioreactor batch cultivation methodologies were employed and compared.…”
Section: Response Surface Methodology (Rotatable Central Composite Dementioning
confidence: 99%
See 1 more Smart Citation
“…Scale-up production of bacterial ALP. Bioreactors, often regarded as the heart of the fermentation process, have helped researchers overcome issues facilitating the scale-up of submerged fermentation from a shake flask to production scale 39 . As this work aims to establish a large-scale fermentation system to evaluate the kinetics of microbial growth in a submerged cultivation system, both shake-flask and stirred-bioreactor batch cultivation methodologies were employed and compared.…”
Section: Response Surface Methodology (Rotatable Central Composite Dementioning
confidence: 99%
“…1. Mathematical experimental designs including the Plackett-Burman design (PBD) and response surface methodology (RSM) are employed to optimize the media constituents during the fermentation process to address the shortcomings of the traditional one-factor-at-a-time approach (OFAT) and to enhance metabolite productivity 13 .…”
mentioning
confidence: 99%
“…Glucose was also documented as the best carbon source in optimizing the production of β- carotene by B. trispora [ 31 ]. Investigation of Jinendiran et al also discovered that glucose gave a maximum production of β -carotene as compared to other carbon sources by Exiguobacterium acetylicum S01 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the recent few years, the production of β -carotene has increased worldwide due to vast applications in various industries. Currently, remarkable achievements have been made in the optimization of medium components, and the optimal composition of media proved to be a key factor for the commercialization of the fermentation operation [ 32 ]. Even though it is the first time that the optimization of carotenoids using a metabolic flux redirecting strategy has been conducted in M. circinelloides , several previous studies demonstrated the metabolic flux redistribution in other microorganisms [ 20 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll is the main instrument responsible for photosynthesis. Carotenoids are natural pigments with substantial applications in nutraceutical and pharmaceutical, food industries ( Jinendiran et al, 2019), it is provide several biological functions in micro-organisms and plants such as in photoprotection (Britton et al, 2004). Herbicides exhibited some phytotoxic effects on crop plants (Sundaru, 1983, Nandihalli and Bhowmik, 1992, Singh et al, 1996, Kushwaha and Bhowmik, 1999, Thapa, 2012, Singh et al, 2016, Tagour and Mosaad, 2017, Saha et al, 2018.…”
Section: Introductionmentioning
confidence: 99%